Willingness and Ability to Pay for Renewable Energy in Jakarta - Whidas Prihantoro; Yuki Mahardhito Adhitya Wardhana; Udi Syahnoedi Hamzah (School of Postgraduate Studies, Diponegoro Univer, 2025)
The Indonesian government is firmly committed to achieving Net Zero Emission (NZE) by 2060. This involves transitioning the electricity sector by progressively replacing fossil fuels with renewable energy sources. The goal is to have a renewable energy mix of at least 23% by 2025 and at least 31% by 2050. This commitment applies to all provinces in Indonesia, including DKI Jakarta Province. This study aims to analyze the willingness and ability to pay DKI Jakarta Province residents for potential changes in energy prices resulting from an energy transition that increases the renewable energy mix. By 2023, the renewable energy mix in Indonesia reaches 13.3%. Coal is still the most widely used energy sources ini Indonesia, reaching 39,7%. This research employs quantitative methodology to ascertain the purchasing ability of the community for electrical energy through questionnaire distribution to PT PLN (Persero) customers. The respondents of this research are PT PLN (Persero) customers with household categories at all levels, which are R1, R2 and R3. The result showed that that a vast majority of respondents (97%) recognize coal as the primary energy source for electricity generation, with 96.3% acknowledging its negative environmental and health effects. Awareness of the government's energy transition policy is high at 97.6%, and 93.3% of respondents support the shift to renewable energy. However, the willingness to pay higher electricity tariffs declines across customer categories, with R1 at 54.13%, R2 at 47.83%, and R3 at 33.33%. The research results on respondents' ability to pay show that R1 category respondents represent 5% of the initial bill. The R2 and R3 categories represent a maximum of 10% of the initial bill.